Implementation of Team-Assited Individualization Instructional Strategies Supported by Geogebra Software to Improve Mathematical Problem Solving Ability - Nasruddin, Nasruddin; Mashuri, Sufri; Jahring, Jahring (FKIP Universitas Lampung, 2019)
Implementation of team assisted individualization instructional strategies supported by GeoGebra software to improve mathematical problem solving ability. Objectives: This quasi-experiment study aims to determine the effectiveness of Team Assisted Individualization (TAI) instructional strategies assisted by Geogebra graphical software to improve students’ mathematical problem solving abilities. Method: By cluster random sampling techniques, 66 students in grade VIII at SMPN 1 Wundulako were selected as sample. Data collection was carried out using pretest and posttest by applying test and non-test instrument. The data analysis was carried out with descriptive and inferential statistics. Findings: The Tukey test results showed that the significance value was 0.005 (α<0.05) with the average scores of the experimental and control classes 80.42 and 76.03. Conclusion: TAI strategy with graphical software is more effective in improving the mathematical problem solving ability than conventional learning. Keywords: Team assisted individualization, GeoGebra, mathematical problem solving ability DOI: http://dx.doi.org/10.23960/jpp.v9.i1.201903